State(s) of negotiation - Müller-Funk, Lea,Fröhlich, Christiane,Bank, André (German Institute of Global and Area Studies (GIGA), 2020)
Between normative aspirations and national interests, forced migrants often become pawns in host states' negotiations with internal and external actors. Focusing on North Africa, the Middle East, and the Horn of Africa, this paper offers an analytical framework to better understand forced migration governance across space and time from a more global, pluralist perspective in a logic of iterative theory-building. We hypothesise that some drivers of forced migration governance are distinct from drivers of migration governance - for example, global policy and conceptions of humanitarian norms and principles play a larger role in the former. We hypothesise that while forced migration governance is negotiated around humanitarian principles, in which international actors, externalisation, and civil society play a crucial role, it also functions as a regime strategy and is driven by certain characteristics of forced migrant groups, including size and perceived identity proximity. Finally, forced migration governance is characterised by strong path dependency.
10419/224836
Keywords: Graue Literatur; Vertreibung; Zuwanderer; Governance; Ursache; Theoriebildung; migration governance; forced migration; stability; Middle East; North Africa; Horn of Africa; regime strategy; crisis